Genetic variants at HbF‐modifier loci moderate anemia and leukocytosis in sickle cell disease in Tanzania. Issue 1 (20th October 2014) - Mtatiro, Siana Nkya; Makani, Julie; Mmbando, Bruno; Thein, Swee Lay; Menzel, Stephan; Cox, Sharon E.
<x xml:space="preserve">Abstract</x> Fetal hemoglobin (HbF) is a recognized modulator of sickle cell disease (SCD) severity. HbF levels are strongly influenced by genetic variants at three major genetic loci, Xmn1‐HBG2, HMIP‐2, and BCL11A, but the effect of these loci on the hematological phenotype in SCD, has so far not been investigated. In a cohort of individuals with SCD in Tanzania (HbSS and HbS/β° thalassemia, n = 726, aged 5 or older), HbF levels were positively correlated with hemoglobin, red blood cell (RBC) indices, mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH), and negatively with white blood cell (WBC) and platelet counts (all P < 0.0001). We subsequently assessed the contribution of the three HbF modifier loci and detected diverse effects, including a reduction in anemia, leukocytosis, and thrombocytosis associated with certain HbF‐promoting alleles. The presence of the 'T' allele at Xmn1‐HBG2 led to a significant increase in hemoglobin (P = 9.8 × 10−3) but no changes in cellular hemoglobin content. Xmn1‐HBG2 'T' also has a weak effect decreasing WBC (P = 0.06) and platelet (P = 0.06) counts. The BCL11A variant (rs11886868‐'C') increases hemoglobin (P = 2 × 10−3) and one of the HBS1L‐MYB variants decreases WBC values selectively (P = 2.3 × 10−4). The distinct pattern of effects of each variant suggests that both, disease alleviation through increased HbF production, and 'pleiotropic' effects on blood cells, are involved, affecting a variety of pathways. Am. J. Hematol. 90:E1–E4, 2015. © 2014 Wiley Periodicals, Inc.